2017
DOI: 10.1145/3064884
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Temporal Activity to Detect Anomalous Behavior in Social Media

Abstract: Social media has become a popular and important tool for human communication. However, due to this popularity, spam and the distribution of malicious content by computer-controlled users, known as bots, has become a widespread problem. At the same time, when users use social media, they generate valuable data that can be used to understand the patterns of human communication. In this article, we focus on the following important question: Can we identify and use patterns of human communication to decide whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…A.F.Costa et al [18] and Y.T.Daniel et al [19] have found that for many ordinary users, when logging in and using these social media, their behavioral records have a significant time distribution. This shows that users may have their own habits of using these social media and these behavior on social media is likely to have a temporal correlation.…”
Section: -Temporal Behavioral Securitymentioning
confidence: 99%
“…A.F.Costa et al [18] and Y.T.Daniel et al [19] have found that for many ordinary users, when logging in and using these social media, their behavioral records have a significant time distribution. This shows that users may have their own habits of using these social media and these behavior on social media is likely to have a temporal correlation.…”
Section: -Temporal Behavioral Securitymentioning
confidence: 99%
“…According to the social interactions between users of the Twitter user to identify the active, passive and inactive users, a supervised machine learning method was proposed to identify social bots on the basis of age, location and other static features of active, passive, and inactive users in the Twitter, as well as interacting person, interaction content, interaction theme, and some dynamic characteristics [23]. A time act model, namely, Act-M, was constructed focusing on the timing of user behavior activities [24], which can be used to accurately determine the interval between different behaviors of social media users to accurately detect malicious users. There have been focused on detecting semi-social bots too.…”
Section: B Social Bots Detectionmentioning
confidence: 99%
“…ž Hacker News. Hacker News is a social news website focused on technology news [13], with functionality very similar to Reddit. The main diference between the two news aggregators is that Hacker News focuses on technology news and has no sub-communities, while Reddit, in general, does not focus on any topic, but supports sub-communities that do.…”
Section: Introductionmentioning
confidence: 99%